Studies of La- and Pr-driven reverse distortion of FeO6 octahedral structure, magnetic properties and hyperfine interaction of BiFeO3 powder. Issue 22 (28th March 2018) - Xiao, RenZheng; Hu, Tao; Yuan, XianBao; Zhou, JianJun; Ma, XiaoQiang; Fu, DeJun
Abstract : Mössbauer spectra of the Bi1− x − y La x Pr y FeO3 ( x = 0 and 0.05; y = 0, 0.10, 0.15 and 0.20) (BLPFO) powders. Abstract : The Bi1− x − y La x Pr y FeO3 ( x = 0 and 0.05; y = 0, 0.10, 0.15 and 0.20) (BLPFO) powders were prepared using a hydrothermal method. The lattice structure of the samples was characterized by X-ray diffraction, which revealed an increase in the lattice constant of the doped samples evidencing the substitution of Bi by La and Pr ions. Raman spectroscopy was used to further analyse the structural distortion in the samples. Scanning electron microscopy was used to characterize the morphology of the samples. The atomic concentrations (%) of La and Pr elements in the samples were detected by Energy Dispersive X-ray spectroscopy. The ferromagnetism of the samples increased with the increase in La and Pr co-doping concentration as observed by vibrating sample magnetometry at room temperature. The evidence of reverse distortion of FeO6 octahedral structure in the La and Pr co-doped samples was revealed by the Mössbauer spectra parameters: Is, Qs, H, Γ, χ 2 and area ratio ( A 1 / A 2 ) of two sextets.